IMPLEMENTATION CHALLENGES OF THE INDEPENDENT CURRICULUM: A QUALITATIVE STUDY AT MTS INSAN MADANI, SITUBONDO - Kulsum, Ummi; Sundarwati, Desi; Sihinda, Vita Nur; Jannah, Nafisah Mafazatul; Puspitasari, Yesi (STKIP PGRI Situbondo, 2024)
A curriculum is a plan and regulation containing objectives, content, learning materials, and teaching methods used as guidelines in teaching and learning activities. The curriculum is the leading guide for educators to ensure every student has access to rigorous academic experiences. The word